Sketching Expert System for Crime Investigation Purposes - Bagus Yudistira; I Ketut Gede Darma Putra; Anak Agung Kompyang Oka Sudana (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
The presence of police sketcher play an important role in making investigation in purpose of making arrestment to fugitive or suspect. The lacking presence of police sketcher is making a lack in investigation process, because lack of information gathered for the further process. This limitation is overcome by developing an expert system using gadget as a helping device to making sketch, with adding sketcher knowledge. Sketching method already been used since long time in process of investigation and effective making the result. The result of expert system on case given showing the system to real object which made sketching reach 85% of accuracy level.